2012
DOI: 10.3390/molecules17032271
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Volatile Composition in Brown Millet, Milled Millet and Millet Bran by Gas Chromatography/Mass Spectrometry

Abstract: Abstract:The volatile compounds from brown millet (BM), milled millet (MM) and millet bran (MB) were extracted using simultaneous distillation/extraction with a Likens-Nickerson apparatus. The extracts were analysed using gas chromatography coupled with mass spectrometry (GC-MS). A total of 65 volatile compounds were identified in all of the samples. Among these compounds, 51, 51 and 49 belonged to BM, MM and MB, respectively. Aldehydes and benzene derivatives were the most numerous among all of the compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 41 publications
6
50
1
Order By: Relevance
“…Sulphur containing compounds that were present include Diethyl disulphide, Benzothiazole. The results that were obtained were in accordance to the research outcomes of Damjan et al (2009) and Liu et al (2012).…”
Section: Volatile Compounds Of Sorghum and Milletsupporting
confidence: 81%
“…Sulphur containing compounds that were present include Diethyl disulphide, Benzothiazole. The results that were obtained were in accordance to the research outcomes of Damjan et al (2009) and Liu et al (2012).…”
Section: Volatile Compounds Of Sorghum and Milletsupporting
confidence: 81%
“…These studies have shown that bound polyphenols possess a higher antioxidant capacity compared to free polyphenols (Liyana-Pathirana & Shahidi, 2006;. In addition, several studies have shown that bound polyphenols in foxtail millet bran could be responsible for antidiabetic and antihypertensive properties (Amadou, Amza, Shi, & Le, 2011;Liu, Tang, Zhang, & Zhao, 2012). Therefore, bound forms of polyphenols have attracted more attention as potential agents for precaution and therapy of oxidative stress-related diseases.…”
Section: Introductionmentioning
confidence: 96%
“…A mass spectrometer [22,23] is an analytical spectroscopic instrument that is primarily concerned with the separation of molecular (and atomic) species according to their mass. The MS does not actually measure the molecular mass directly, but rather the mass-to-charge ratio of the ions formed from the molecules.…”
Section: Gas Chromatography and Gas Chromatography/mass Spectrometer mentioning
confidence: 99%